Effect of yttrium doping on the photocatalytic properties of ZnO thin films - Hrytsak, L.; Turko, B.; Vasil’ev, V.; Eliyashevskyy, Y.; Kostruba, A.; Hrytsak, A. (Physics and Chemistry of Solid State, 2023)
Zinc oxide films with different levels of yttrium doping are deposited on glass substrates, using radio-frequency magnetron sputtering. Photocatalytic properties were investigated for such Y-doping weight concentration: 0, 2.4, 3.9, 4.7 wt. %. The studies showed that the Y-doping significantly improves the photocatalytic activity of the ZnO thin films. It was shown that the ZnO:Y 3.9 wt. % presents the highest degradation efficiency of 100 % during 80 minutes and the largest rate constant 9.6 · 10-2 min-1 among all samples.